BORISAV STANKOVIĆ AND IVO ANDRIĆ IN THE LIGHT OF THE NEW CURRICULUM STUDIES - Jована Н. Давидовић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2015)
The paper comprises two parts: the analytical-interpretative and the methodical part. The focus of the first part of the paper is a comparative study of The godly people by Borisav Stanković and Temptation and Death in Sinan's tekke by Ivo Andrić. By means of a comparative analysis, the paper examines the impact of the mythic image of the world and the traditional culture in these works. The paper is primarily focused on the impact of the mythic time and space, the basic categories of the mythic image of the world. Traces of traditional cultures are found in the binary opposition of black and white, but also in the protective role of the stone and its ability to bind itself to the souls of the dead. The paper also compares Stanković's and Andrić's godly people. At the end "stand" women at the gate. The paper aims to provide an impetus for the creation and modernization of the subject the Serbian Language and Literature, with the goal of emphasizing the principle of a scientific approach in the contemporary teaching context and encouraging active and creative reading. Through the application of contemporary findings in teaching methodology, this paper fights against every scheme, stereotype and rote learning, bound by the artistic essence of literature.